Comparative analysis of respiratory health profile among female beedi and non-beedi workers in a district of West Bengal - Biswas, Sujata; Bharti, Nisha; Basu, Gandhari (Asian Journal of Medical Sciences, 2021)
Background: Beedi workers are more prone to develop chronic respiratory diseases over time. Aims and Objectives: The present research aimed to investigate and compare the respiratory health profile and the factors associated among the beedi workers and non-beedi workers. Materials and Methods: An analytical, community based, cross sectional study was conducted among 60 female beedi and non-beedi workers. Multistage sampling was used to select three wards out of twenty wards under a municipality of the study district. After interview with a pre-designed structured questionnaire, the respondents were examined clinically and pulmonary function test was done using a portable spirometer. Results: All beedi workers were married and 23.3% were illiterate. Most of them had 1to 10 years exposure. Half of them initiated their work between 11 to 20 years. Rate of tobacco smoking, obesity, hypertension, asthma, diabetes was high among beedi workers. Forced Vital Capacity, Forced Expiratory Flow 25-75 and Peak Expiratory Flow Rate were significantly more among non-beedi workers. Forced Expiratory Volume in 1st second was more among non-beedi workers but FEV1/FVC ratio was same for both the group. Conclusion: Significantly better respiratory health profile of non-beedi workers have reflected beedi binding as a reason behind chronic respiratory disease. Therefore, awareness generation session regarding occupation based adverse effects and safety measures must be conducted at regular interval to make the working condition favorable.